Use of aI techniques and updating in geomechanical characterisation - Miranda, Tiago F. S. (2007)
Fundação para a Ciência e a Tecnologia (FCT) - projecto POCI/ECM/57495/2004 "Geotechnical Risk in Tunnels for High Speed Trains"